The response of microbiome assembly within different niches across four stages to the cultivation of glyphosate-tolerant and conventional soybean varieties - Chao, Shengqian; Sun, Yu; Zhang, Yin; Chen, Yifan; Song, Lili; Li, Peng; Tang, Xueming; Liang, Jingang; Lv, Beibei (Frontiers in Microbiology, 2024)
Plants are inherently connected with the microbiome, which plays a crucial role in regulating various host plant biological processes, including immunity, nutrient acquisition, and resistance against abiotic and biotic stresses. Many factors affect the interaction between plants and microbiome. In this study, microbiome samples were collected from five niches (bulk soil, rhizoplane, root endosphere, phylloplane, and leaf endosphere) across four developmental stages (seedling, flowering, podding, and maturity) of various soybean varieties. Composition and structure of bacterial and fungal communities were analyzed using 16S rRNA gene and ITS (Internally Transcribed Spacer) region amplicon sequencing. It was observed that both niches and developmental stages significantly impact on the assembly and composition of soybean microbiome. However, variety, presence of a transgene, and glyphosate application had minimal effects on microbial communities. The dominant microbiome varied across the five niches, with most containing beneficial microbial communities capable of promoting plant growth or increasing disease resistance. Types and abundance of the dominant microbes affected network stability, potentially resulting in functional changes in different ecological niches. This study provides theoretical evidence for microbial protection of plants against diseases and demonstrates that systematic analysis of the composition and diversity of soybean microbiomes can contribute to the development of biological control technologies.